2018
DOI: 10.3168/jds.2017-13892
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the physical forms of starter and forage source on growth performance and blood metabolites of Holstein dairy calves

Abstract: The objective of this study was to investigate the effects of the physical forms of starter and forage sources on feed intake, growth performance, rumen pH, and blood metabolites of dairy calves. Forty male Holstein calves (41.3 ± 3.5 kg of body weight) were used (n = 10 calves per treatment) in a 2 × 2 factorial arrangement of treatments with the factors being physical forms of starter (coarse mash and texturized) and forage source [alfalfa hay (AH) and wheat straw (WS)]. Individually housed calves were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 39 publications
5
18
0
1
Order By: Relevance
“…Previous work reported higher VFA concentration when steers were fed with processed grains (Murphy et al, 1994), which was due to greater ruminal starch digestibility (Theurer et al, 1999;Gimeno et al, 2015). The range of ruminal VFA concentrations in the current study was within the ranges reported for dairy calves in previous studies (Khan et al, 2008;Mirzaei et al, 2016;Omidi-Mirzaei et al, 2018). The difference in the molar percentage of individual VFA in the rumen (greater propionate and butyrate instead of acetate and BCVFA) in calves fed SFC diets partly explains improved ADG from the energetic efficiency point of view compared with the GRC diets.…”
Section: Effect Of Corn Processingsupporting
confidence: 80%
See 1 more Smart Citation
“…Previous work reported higher VFA concentration when steers were fed with processed grains (Murphy et al, 1994), which was due to greater ruminal starch digestibility (Theurer et al, 1999;Gimeno et al, 2015). The range of ruminal VFA concentrations in the current study was within the ranges reported for dairy calves in previous studies (Khan et al, 2008;Mirzaei et al, 2016;Omidi-Mirzaei et al, 2018). The difference in the molar percentage of individual VFA in the rumen (greater propionate and butyrate instead of acetate and BCVFA) in calves fed SFC diets partly explains improved ADG from the energetic efficiency point of view compared with the GRC diets.…”
Section: Effect Of Corn Processingsupporting
confidence: 80%
“…A successful calf rearing program aims to maximize the growth potential of dairy calves early in life. Readily fermentable carbohydrates and processing of grains play an important role in encouraging early starter feed intake and promoting excellent growth (Bateman et al, 2009;Omidi-Mirzaei et al, 2018). Corn grain ferments more slowly than barley or wheat, and slower rates of ruminal digestion increase the quantity of starch bypassing the reticulorumen (Khan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Starter feed diets for dairy calves are typically based on concentrate and a source of forage (hay or straw) and therefore are almost dry (Beiranvand et al, 2014(Beiranvand et al, , 2016Pazoki et al, 2017;Omidi-Mirzaei et al, 2018). Earlier studies with heifers have revealed decreased (Khan et al, 2014) or no changes (Thomas et al, 1961) in DMI with increasing dietary moisture.…”
Section: Introductionmentioning
confidence: 99%
“…Total mixed rations with higher moisture levels are in cake form (and very sticky; Beiranvand et al, 2016) and thought to be more susceptible to spoilage (especially at higher environmental temperatures; Felton and DeVries, 2010), and DMI will be decreased if feed is spoiled or not fresh, leading to increased feed waste and increased cost. Most forages offered to young calves are low in sugars and higher in more poorly fermented fiber (Beiranvand et al, 2014;Omidi-Mirzaei et al, 2018). Reconstituting hay by soaking in water can increase fiber digestibility by decreasing the ruminal digestion lag time (Pasha et al, 1994) or increase cation exchange capacity for some minerals (Van Soest, 1994), and therefore increase rumen buffering capacity and fecal consistency.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary fibre is important for promoting rumination and maintaining rumen health and also provides energy to the host animal for maintenance and production (1,2) . Fibre degradation in the rumen is a complex process that needs a wide range of microorganisms to work as a consortium, including fungi, protozoa, bacteria and methanogens (3,4) .…”
mentioning
confidence: 99%